Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (x - 78) . 26 = 40
=>x-78 = 40 : 26 = 20/13
=> x = 78 + 20/13
=> x = 1034/13
b) 39 . (x-5) =39
=>x-5=39:39=1
=>x=1+5=6
c) 30- ( 52 - x) =90
=>30-52+x=90
=>-22+x=90
=>x=90-(-22)
=>x=112
d) (x-12) : 5 =2
=>x-12=2.5=10
=>x=10+12=22
x-7=(-3)-8
<=> x=7-3-8
<=>x=-4
5-x=12
<=> -x=-5+12
<=> -x=7
<=> x=-7
\(-12.\left(x-5\right)+7.\left(3-x\right)=5\)
\(-12x+60+21-7x=5\)
\(-12x-7x+81=5\)
\(-19x+81=5\)
\(-19x=5-81\)
\(-19x=-76\)
\(x=\left(-76\right):\left(-19\right)\)
\(x=4\)
Học tốt nhé bn !!!!!
-12 ( x- 5 ) + 7.(3-x) =5
-12x+60+21-7x =5
60+21-5 =12x+7x
76 =19x
x = 76:19
x = 4
c.53 ×39+47×39 + 53 x 21 + 47 x 21=6000
D . 2 x 53 x 12 + 4 x 6 x 87 - 3 x 8 x 40=2400
học tốt
C ) = 39 . ( 53 + 47 ) + 21 . ( 53 + 47 )
= 39 . 100 + 21 . 100
= (39 + 21) . 100
= 60 . 100
= 6000
D ) = 24 . 53 + 24 . 87 - 24 . 40
= 24 . ( 53 + 87 - 40 )
= 24 . 100
= 2400
[(6x-39):7]x4=12
[(6x-39):7]=12:4=3
(6x-39)=3x7=21
6x=21+39=60
x=60:6=10
39=11*x
x=39:11
=39/11
Chúc bạn may mắn!
39=11*x
x=39:11
x=39/11